2020
DOI: 10.3390/biomedicines8070207
|View full text |Cite
|
Sign up to set email alerts
|

Serum γ-Glutamyltransferase Concentration Predicts Endothelial Dysfunction in Naïve Hypertensive Patients

Abstract: Background: Serum gamma-glutamyltransferase (γ-GT) is recognized as a risk factor for cardiovascular diseases (CV). Traditional cardiovascular risk factors mediate endothelial dysfunction. Aim: to evaluate a possible correlation between serum γ-GT and endothelium-dependent vasodilation in naïve hypertensives. Methods: We enrolled 500 hypertensives. Endothelial function was studied by strain-gauge plethysmography. Receiver operating characteristic (ROC) analysis was used to assess the predictive value of γ-GT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(36 reference statements)
0
2
0
3
Order By: Relevance
“…It contributes to endothelial dysfunction, arterial stiffness, and dysregulated sympathetic nervous system activity, all of which play significant roles in the pathogenesis of hypertension. 29–38 Mounting evidence suggests a strong association between insulin resistance and cognitive decline; chronic exposure to insulin resistance is linked to neuroinflammation, oxidative stress, and impaired insulin signaling in the brain, leading to cognitive impairments such as reduced executive function, memory deficits, and an increased risk of dementia. 39–41 In addition to cognitive decline, insulin resistance also contributes to physical impairments commonly observed in hypertensive individuals, including endothelial dysfunction, dyslipidemia, obesity, and an overall increased risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…It contributes to endothelial dysfunction, arterial stiffness, and dysregulated sympathetic nervous system activity, all of which play significant roles in the pathogenesis of hypertension. 29–38 Mounting evidence suggests a strong association between insulin resistance and cognitive decline; chronic exposure to insulin resistance is linked to neuroinflammation, oxidative stress, and impaired insulin signaling in the brain, leading to cognitive impairments such as reduced executive function, memory deficits, and an increased risk of dementia. 39–41 In addition to cognitive decline, insulin resistance also contributes to physical impairments commonly observed in hypertensive individuals, including endothelial dysfunction, dyslipidemia, obesity, and an overall increased risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…AST is generally considered a marker of myocardium and liver damage. Perticone et al reported that AST was closely related to the endothelial function, as evaluated by strain-gauge plethysmography, in both univariate linear analysis and a stepwise multivariate regression model ( 41 ). This is consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Одной из основных функций GSH явля-ется перенос аминокислот в клетку с помощью γ-глутамилтрансферазы (GGT), в результате вне клетки остаётся дипептид -цистеинилглицин (CysGly), который под действием дипептидаз может расщепляется до аминокислот [1]. Показано, что сывороточная GGT является фактором риска развития сердечно-cоcудистых заболеваний [14,15], что может быть связано с увеличением концентрации продукта реакции -цистеинил-глицина (CysGly). CysGly, в силу наличия SH группы, участвует в превращении Fe 3+ в Fe 2+ и таким образом провоцирует формирование оксидантного стресса.…”
Section: результаты и обсуждениеunclassified
“…Следствием этого является, например, рост окисленной формы липопротеидов низкой плотности и активация воспалительных процессов, т.е. атерогенез [14,15]. У женщин I группы уровень CysGly был на 23,2% (р<0,001 выше результата II группы и в 1,8 раза выше показателей группы контроля (р<0,001).…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation